Hypertension and Cardiovascular Disease: Contributions of the Framingham Heart Study - Stanley S. Franklin; Nathan D. Wong (2013)
This is a historical review of the contribution of the Framingham Heart Study to our understanding of the epidemiology of blood pressure (BP) and cardiovascular disease (CVD). Framingham investigators initially explored the epidemiological relationship of various BP components to coronary heart disease in men and women and how this risk is further modified by age, that is, how diastolic blood pressure (DBP) is the stronger predictor of coronary heart disease risk in young people versus systolic blood pressure (SBP) in middle-aged and elderly people. Framingham investigators then examined the natural history of various BP components over a 30-year follow-up in normotensive and untreated hypertensive individuals and showed how this provides hemodynamic insights into the importance of pulse pressure as a marker of large artery stiffness in middle-aged and elderly people. Importantly, pulse pressure was also found to be superior to SBP or DBP as a predictor of coronary heart disease in a middle-aged and elderly Framingham population. Lastly, dual models of SBP with DBP and pulse pressure with mean arterial pressure were superior to single BP component models for predicting CVD events; thus, increases in both peripheral vascular resistance and central large artery stiffness contribute to CVD in varying proportions depending on age. Furthermore, the Framingham Heart Study provided evidence that DBP <70 mm Hg with SBP ≥120 mm Hg was associated with a CVD risk equivalent to approximately 20 mm Hg of additional elevation in SBP, thus further supporting the importance of large artery stiffness as a CVD risk factor in elderly people. These original Framingham studies have contributed greatly to BP risk classification tables for the "Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure" and for the European Society for Hypertension. Moreover, Framingham originally brought attention to hypertension, which is now the leading cause of mortality globally.